'I'm blind, not deaf!': Hegemonic soundscapes and resistant hearing in Dario Argento's Suspiria and Inferno. Issue 1 (1st January 2019) - Pollard, Damien
This article demonstrates that the soundscapes of Dario Argento's Suspiria (1977) and Inferno (1980) represent key battlegrounds upon which dominant, hegemonic forces face challenge from those who have learned to adopt insurgent modes of hearing. This article adopts a methodology of attending foremost to the diegetic soundscapes that Argento constructs: the soundscapes that are ostensibly audible to the characters within the diegesis. This methodology avoids the critical tendency within studies of Argento to fixate on his films' visual or musical elements and reveals such soundscapes to be fundamental to the flows of power and resistance operative in each film. In Suspiria, the conflict between a hegemonic soundscape and a character's rebellious hearing unfolds in a fairy tale microcosm, but in Inferno Argento expands the scope and the stakes of this tension, re-staging it in the historically and politically specific setting of a globalized, neo-liberal New York City.